2011
DOI: 10.1055/s-0031-1296899
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amide Derivatives of [6-(3,5-Dimethylpyrazol-1-yl)-3(2H)-pyridazinone-2-yl]acetic Acid and Their Analgesic and Anti-inflammatory Properties

Abstract: Summary A series of structurally different amide derivatives of [6-(3,5-dimethylpyrazol-1-yl)-3(2H)-pyridazinone-2-yl]acetic acid were prepared and tested for their analgesic and anti-inflammatory activity in vivo by using p-benzoquinone-induced writhing test and carrageenan-induced hind paw edema model, respectively. The analgesic and anti-inflammatory activity of the compounds 6a and 6b were equipotent, and 6m was more potent than acetyl salicylic acid (CAS 50-78-2) as an analgesic and indometacin (CAS 53-86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Treatment of compound 13 with acetylacetone afforded 3‐chloro‐6‐(3,5‐dimethyl‐1 H ‐pyrazol‐1‐yl)pyridazine ( 14 ) as previously described by Süküroglu et al . Hydrolysis of compound 14 by refluxing in acetic acid in presence of sodium acetate furnished 6‐(3,5‐dimethyl‐1 H ‐pyrazol‐1‐yl)pyridazine‐3(2 H )‐one ( 15 ) as reported by Banoglu et al . N ‐Alkylation of 15 with benzyl bromide, 4‐bromobenzylbromide, and/or N ‐bromomethylphthalimide in dry dimethylformamide in the presence of anhydrous potassium carbonate furnished the desired compounds 16a–c (Scheme ).…”
Section: Resultsmentioning
confidence: 77%
“…Treatment of compound 13 with acetylacetone afforded 3‐chloro‐6‐(3,5‐dimethyl‐1 H ‐pyrazol‐1‐yl)pyridazine ( 14 ) as previously described by Süküroglu et al . Hydrolysis of compound 14 by refluxing in acetic acid in presence of sodium acetate furnished 6‐(3,5‐dimethyl‐1 H ‐pyrazol‐1‐yl)pyridazine‐3(2 H )‐one ( 15 ) as reported by Banoglu et al . N ‐Alkylation of 15 with benzyl bromide, 4‐bromobenzylbromide, and/or N ‐bromomethylphthalimide in dry dimethylformamide in the presence of anhydrous potassium carbonate furnished the desired compounds 16a–c (Scheme ).…”
Section: Resultsmentioning
confidence: 77%
“…The other amide derivatives and parent carboxylic acid molecule generally resulted in lower activity to reference drugs. Inhibitor activity of the active compounds on COX isoforms was also tested by using in vitro COX inhibitor screening assay and found that these derivatives did not exert their analgesic and anti-inflammatory activities through COX inhibition and that other mechanisms might be involved (Banoğlu at al., 2005). Despite the increasing implication of the permeability transition pore (PTP) in the pathophysiology of neurodegenerative diseases, few selective PTP inhibitors have been reported so far.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Among them, pyrazole-carboxamide derivatives have been shown to exhibit antimycobacterial, antifungal and antiviral activities (Sun & Zhou, 2015;Yan et al, 2018;Comber et al, 1992). In the course of our ongoing research into bioactive pyrazole derivatives (Banog lu et al, 2005;Ş ü kü rog lu et al, 2005;Ergü n et al, 2010;Ç alışkan et al, 2011;Levent et al, 2013;Cankara Pirol et al, 2014), we have relied on the aforementioned biological properties of pyrazole-carboxamides and designed novel pyrazole-3-carboxamide derivatives for their potential antimicrobial activity. In this work, we report the crystallographic characterization and Hirshfeld surface analysis of one of these compounds bearing the 2,4dichlorobenzyl substituent at one of the pyrazole nitrogen atoms.…”
Section: Chemical Contextmentioning
confidence: 99%